Apakah modal sosial dan kearifan lokal memengaruhi kewirausahaan? Bukti empiris wirausaha Bugis - Muhajir, Muhammad Nur Alam; Hamida, Ambas; Erwin, Erwin; Jabani, Muzayyanah (Jurnal Ilmu Manajemen, 2023)
Social capital and local wisdom predicted affecting entrepreneurial spirit on the Bugis people in Indonesia who have the value of local wisdom Warani Na Getteng. This study aims to analyze the impact or influence of the value of the local wisdom of Warani Na Getteng on the entrepreneurial spirit of the Bugis community; analyze the influence of social capital on the entrepreneurial spirit of the Bugis community. This study uses primary data in the form of a questionnaire or questionnaire distributed to 30 respondents using an accidental sampling technique. Using Ordinary Least Square (OLS) regression to determine the effect between variables, the authors found that the value of Warani Na Getteng's local wisdom positively influenced the entrepreneurial spirit. The exact estimation results also found that social capital positively affects the spirit of entrepreneurship. This research implies that this study provides an empirical contribution to the literature on the impact of local wisdom values and social capital on the entrepreneurial spirit. Besides that, the policy recommendation related to the results of this study is that strengthening the values of local wisdom in the community is necessary to increase the spirit of entrepreneurship, especially for people with low incomes.